La autoestima y su relación con el desarrollo cognitivo de las niñas y niños de segundo, tercero y cuarto grado del subnivel básica elemental, de educación general básica de la escuela fiscal mixta “Luis Alfredo Samaniego Arteaga” del cantón Catamayo, provincia de loja, año lectivo 2012 -2013 - Jaramillo Ortiz, Andrea Paola (2014)
The proposed investigation was guided to the determination of the existent relationship among the self-esteem and the girls' development cognitive and second children, third and quarter grade of the Elementary Basic Subnivel Basic Elementary, of Basic General Education of the mixed fiscal school "Luis Alfredo Samaniego Arteaga". In the development of the investigative process it was necessary the use of the scientific method, the descriptive method, the analytic method - synthetic and the hypothetical method - deductive. The structured interview and the survey, as well as the interview guide and the questionnaire, they were the techniques and instruments that applied the director as well as to the educational family parents and students, respectively, they allowed to obtain the required information. The investigative universe was conformed by 118 distributed human talents in the following way: a director, fourteen educational, self-esteem, while alone 40% of the students, they demonstrate a low self-esteem, in spite of the fact that the educational ones, somehow, they are using appropriate methodologies to motivate the self-esteem and the development cognitive, what has caused that the level self-esteem in the students is low. The family parents also affirm that the behavior of their children is not the appropriate one for that that the educational ones somehow should help to motivate. As main conclusion you ended up settling down that the educational ones if they use the processes of motivating the self-esteem and the development cognitive of this important value so that the boy has an excellent development in the class and society, however it is not the appropriate form, since not all have the same techniques and methods that you/they help the children. It is recommended the Director of the institution to carry out administrations in the face of the pertinent authorities, to achieve the necessary help that contributes to the solution of the problem that the educational center, scenario of the investigation lives.